(untitled) (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2023)
Angus McFadzean, Program Director of the Oxford University Summer School for Adults, writer, and researcher, categorized in 2017 the suburban fantastic - a cinematographic subgenre encompassing adventure films with elements of horror, fantasy, and science fiction from the 1980s such as Back to the Future, E.T. and The Goonies. Suburban Fantastic, marked by nostalgia for the American post-war period, was linked to the context of Reaganist entertainment, having its narratives built from the validation of a white and androcentric “American Dream.” In this interview, we discussed the subgenre, its syntactic, semantic, aesthetic, and sociopolitical elements, its return in the decade in films and series such as Stranger Things, and its adaptations to other markets such as the British and Brazilian.